Electrophysiological Study of the Tibial Nerve Across the Tarsal Tunnel in Distal Symmetric Diabetic Polyneuropathy. (February 2022) - Mondelli, Mauro; Aretini, Alessandro; Ginanneschi, Federica
Abstract : Objective: The aim of the study was to demonstrate abnormalities of motor conduction of the tibial nerve across the tarsal tunnel in type 2 diabetes. Design: One hundred twenty-four consecutive patients (mean age = 66.6 yrs, 62.1% male) with distal symmetric diabetic polyneuropathy clinically diagnosed were prospectively enrolled. Nerve conduction studies of deep peroneal, tibial, superficial peroneal, medial plantar, and sural nerves and standard needle electromyography in the lower limbs were performed. Demographic, anthropometric, and clinical findings were collected. Results: Motor conduction velocity of the tibial nerve across tarsal tunnel was slowed in 60.5% of patients; another 4% showed conduction block across tarsal tunnel without reduction of motor conduction velocity. Overall percentage of abnormalities across tarsal tunnel (64.5%) exceeds that of the sensory conduction velocities of proximal sural and superficial peroneal nerves. Abnormal tibial motor conduction velocity across tarsal tunnel represents the most common abnormality among all motor nerve conduction study parameters and significantly correlates with hemoglobin level, diabetic neuropathic index score, and diabetic complications frequency. Conclusions: Tibial conduction abnormalities across tarsal tunnel are the most sensitive motor parameter in distal symmetric diabetic polyneuropathy, second only to conduction abnormalities of sensory/mixed distal nerves of the feet. The use of nerve conduction studies across tarsal tunnel of the tibial nerve may be useful in the electrophysiological protocol to confirm the diagnosis of distal symmetric diabetic polyneuropathy.